Feature extraction of power disturbance signal using time frequency analysis - 434810 Norsabrina Sihab (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2006